Whether individual characteristics are related to organizational affiliation - Mhd. Sarif, Suhaimi; Ismail, Yusof (2010)
One’s affiliation with formal and informal organizations tends to reflect dominant attributes or orientation of the organizations. One’s fit with an organization will make him continue his membership; a mismatch will separate the two. Members of two different organizations might face difficulties in their interactions with members of other organizations, and consequently could not work on joint projects. It is therefore important that different organizations become aware of dominant attributes of members of their interacting organizations to facilitate their communication and work on joint projects. The objective of the study is to identify common traits that are shared by members of selected Islamic-related organizations. The study used an open-ended instrument to solicit the opinions on positive and negative attributes perceived by a friend of one who is affiliated with an Islamic organization. The instrument was administered on a group of eighty (n=80) students who studied Business Ethics in a public university in Malaysia The study content analyzed the attributes, and collapsed them into common categories. The authors believe that the current preliminary study is important in harmonizing the relations between various Islamic organizations.